Effect on Blood Pressure of Daily Lemon Ingestion and Walking - Yoji Kato; Tokio Domoto; Masanori Hiramitsu; Takao Katagiri; Kimiko Sato; Yukiko Miyake; Satomi Aoi; Katsuhide Ishihara; Hiromi Ikeda; Namiko Umei; Atsusi Takigawa; Toshihide Harada (Journal of Nutrition and Metabolism)
Background. Recent studies suggest that the daily intake of lemon (Citrus limon) has a good effect on health, but this has not been confirmed in humans. In our previous studies, it was observed that people who are conscious of their health performed more lemon intake and exercise. An analysis that took this into account was required. Methodology. For 101 middle-aged women in an island area in Hiroshima, Japan, a record of lemon ingestion efforts and the number of steps walked was carried out for five months. The change rates (Δ%) of the physical measurements, blood test, blood pressure, and pulse wave measured value during the observation period were calculated, and correlations with lemon intake and the number of steps walked were considered. As a result, it was suggested that daily lemon intake and walking are effective for high blood pressure because both showed significant negative correlation to systolic blood pressure Δ%. Conclusions. As a result of multiple linear regression analysis, it was possible that lemon ingestion is involved more greatly with the blood citric acid concentration Δ% and the number of steps with blood pressure Δ%, and it was surmised that the number of steps and lemon ingestion are related to blood pressure improvement by different action mechanisms.